First, let's find the first derivative using implicit differentiation. We have the equation:
x^2 - y^2 = 1
Differentiating both sides with respect to x, we get:
2x - 2y(dy/dx) = 0
Now, solve for dy/dx:
2y(dy/dx) = 2x
(dy/dx) = 2x/2y
(dy/dx) = x/y
Now, let's find the second derivative by differentiating dy/dx with respect to x:
d^2y/dx^2 = (d/dx)(x/y)
To differentiate the right side, we will use the quotient rule which states that:
(d/dx)(u/v) = (vu' - uv')/v^2
In this case, u = x and v = y. So we get:
u' = d/dx(x) = 1
v' = d/dx(y) = dy/dx (since we don't have an explicit expression for y, we will leave it as dy/dx)
Now, applying the quotient rule:
d^2y/dx^2 = (y(1) - x(dy/dx))/y^2
We already found (dy/dx) = x/y, so we can substitute it back in:
d^2y/dx^2 = (y - x(x/y))/y^2
Simplify:
d^2y/dx^2 = (y^2 - x^2)/(y^3)
So the second derivative is:
d^2y/dx^2 = (y^2 - x^2)/(y^3)
use implicit differentiation to find the second derivative.
x^2-y^2=1
1 answer